Monitoring Marcellus: A Case Study of a Collaborative Volunteer Monitoring Project to Document the Impact of Unconventional Shale Gas Extraction on Small Streams. (20th May 2016) - Wilderman, Candie C.; Monismith, Jinnieth
The rapid growth of the natural gas extraction industry in Pennsylvania and neighboring states has stirred concerned citizens to seek ways to collect data on water quality impacts from the extraction activities. As a response to requests from community members, the Alliance for Aquatic Resource Monitoring (ALLARM) developed a volunteer-friendly protocol in 2010 for early detection and reporting of surface water contamination by shale gas extraction activities in small streams. To date, ALLARM has trained more than 2, 000 volunteers in Pennsylvania, New York, and West Virginia to monitor water quality (conductivity, barium, strontium, and total dissolved solids) and physical parameters (stream stage and visual observations) prior to, during, and after shale gas wells have been developed. This paper documents the operational models of Public Participation in Scientific Research (PPSR) used by ALLARM, describes the volunteer monitoring protocol developed, and examines three years of water quality results from hundreds of monitoring sites in Pennsylvania and New York. The majority of watersheds monitored are small, forested, headwater streams. Results indicate that mean conductivity in streams is strongly and positively related to the percentage of development and the percentage of limestone in the watersheds. Mean conductivity is not significantly related to number or density of drilled wells, although the dataset did not lend itself to finding a signal from shale gas activities because only 20% of the watersheds had wells drilled at the time of sampling. This fact enables the use of these data as baseline data for future documentation of shale gas impacts on water quality. Volunteers have reported multiple cases of visual pollution related to shale gas activities, but have not identified water contamination events based on stream water chemistry. The results of the volunteer dataset are compared with results from the scientific literature, affirming the credibility and usefulness of the data. Some lessons learned from this project include: The importance of strong and timely support to volunteers to ensure accurate reporting in real-time; the unique role that citizen scientists can play in a rural landscape where well sites are remote and government oversight is not practical; and the importance of customizing a PPSR operational model to fit the goals and scale of the project. Recommendations for continued collection and analysis of data include: 1) develop and implement an intentional study design to monitor those watersheds that now have baseline data once drilling begins, 2) target watersheds whose characteristics are under-represented in this dataset, 3) consider the analysis of additional parameters and the monitoring of high risk systems, 4) develop a central, user-friendly database for volunteers to submit their own data and receive preliminary analyses, and 5) partner with other volunteer data collectors to collaborate with data analysis and interpretation.